Local People's Political Thought Against Changes in Elite Political Decrees of the Ruler - Hadiati, Tri Lestari; Utomo, Darmawan Tri Budi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
Local people in the North Semarang area continue to aggregate and articulate critical political thoughts, pressing political thinking, and having a strong influence on the ruling elite's political decisions in the city of Semarang. This has been done by local people starting in 2004 until now—for example, Kanjengan Mall in the Johar market area, which investors from PT contracted. Pagar Gunung Kencana, in 2004 has expired. However, Jamaah Peduli Dugder in the North Semarang who always monitor the area say, there is still a development of the Johar market area, the Kauman area, and Malay villages that are not right and lack the attention of local elites and slow development. This research problem formulation is how does the community build the strength of its political thinking? The purpose of this study is to analyze the results of local people's political thinking on changes in elite political decisions and to analyze them with the approach of the power of civil society. This research's methodology was qualitative methodology, which was supplemented by descriptive analysis, including conducting in-depth interviews. In addition to primary data collection, secondary data collection from relevant documents was then analyzed. The conclusion of the political thinking of the local community on the Dugderan tradition is very strong. This resulted in a change in the political decisions of the elite who were then pro-local people.